Fibroblast growth factor 21 in metabolic syndrome - Yang, Ming; Liu, Chongbin; Jiang, Na; Liu, Yan; Luo, Shilu; Li, Chenrui; Zhao, Hao; Han, Yachun; Chen, Wei; Li, Li; Xiao, Li; Sun, Lin (Frontiers in Endocrinology, 2023)
Metabolic syndrome is a complex metabolic disorder that often clinically manifests as obesity, insulin resistance/diabetes, hyperlipidemia, and hypertension. With the development of social and economic systems, the incidence of metabolic syndrome is increasing, bringing a heavy medical burden. However, there is still a lack of effective prevention and treatment strategies. Fibroblast growth factor 21 (FGF21) is a member of the human FGF superfamily and is a key protein involved in the maintenance of metabolic homeostasis, including reducing fat mass and lowering hyperglycemia, insulin resistance and dyslipidemia. Here, we review the current regulatory mechanisms of FGF21, summarize its role in obesity, diabetes, hyperlipidemia, and hypertension, and discuss the possibility of FGF21 as a potential target for the treatment of metabolic syndrome.